Vibration analysis approach to model incremental wear and associated sound in multi-contact sliding friction mechanisms - Basit, Kanza; Shams, Hamza; Khan, Muhammad Ali; Mansoor, Asif (American Society of Mechanical Engineers (ASME), 2023)
This paper proposes a simplistic approach toward estimating incremental wear in a multi-contact scenario using a vibrational analysis approach and in turn goes a step forward to model its associated sound. Predicted wear depth and frictional sound are compared to the experimental values obtained using a standardized pin-on-disc tribometer setup affixed with a free-field microphone to capture air-borne noise. The results show good conformity between the proposed analytical model values and the standardized experiments, hence ensuing that within certain limitations, the proposed model and the intended approach can effectively be used as a good estimator of wear and its sound in a multi-contact scenario.
Keywords: contact; dry friction; sliding; frictional noise; tribological conditions; wear